Electron-Impact Ionization of Se16+ and Ser(17+) Ions - BLEDA, ERDİ ATA; ALTUN, ZİKRİ (IOP PUBLISHING LTD, 2015)
Electron-impact ionization cross sections for Se16+ and Se17+ ions have been calculated using semirelativistic configuration-average distorted-wave (CADW) method for both the direct and indirect ionization contributions. The excitation-autoionization contributions originating from the excitations of 2s and 2p subshels were calculated using a semirelativistic level to level distorted-wave (LLDW) method. Direct ionization cross section calculations involving 2s,2p,3s, and 3p subshells were also calculated using the LANL collisional atomic code and comparisons are made.